COMMUNITY SATISFACTION INDEX (SMI) REPORT AT SMKN 1 CIBINONG - Kulsum, Umi; Taufik, Trias Tino (Jurnal Pensil : Pendidikan Teknik Sipil, 2022)
The purpose of this study was to determine and analyze the level of community assessment of the performance of learning services at SMKN 1 Cibinong Bogor. As it is known, Vocational High Schools (SMK) can be viewed as an institution that offers services in the form of education processes, especially education services as a continuation of first-level education (SMP) and graduates of Madrasah Tsanawiyah (MTs). The main goal of a service agency is how its customers get the satisfaction they expect. When observed. The main customers of a Vocational High School (SMK) are students and parents of students. Therefore it can be said that the satisfaction of parents and students in general and the wider community in general is a priority that must be put forward. With regard to the services offered by SMKN 1 Cibinong, the obligation to carry out education and teaching is the most important activity and is directly related to students. To find out how the service performance of SMKN 1 Cibinong in implementing education and teaching will be measured by how the satisfaction of students who take part in learning activities. The method carried out is by surveying students and conducting the survey referring to the Regulation of the Minister for Administrative Reform and Bureaucracy No. 16 of 2014 concerning Guidelines for Survey of Community Satisfaction on Public Service Delivery. To obtain the Community Satisfaction Index (IKM) value the following formula is used: IKM =( Total of Perceived Value per Element / Total Elements filled in) x Weighted Value. Meanwhile, to obtain the conversion value of the IKM result from the Service Unit IKM Value x 25, the result for the Community Satisfaction Index (IKM) Value of SMKN 1 Cibinong in 2017 is 81.88 with Service Quality B and Service Unit Performance Good.